Unicorn power! - Tamaki, Mariko (Tamaki, Mariko. Lumberjanes, 2019)
While following April who wants to climb a mysterious mountain near Miss Qiunzella Thiskwin Penniquiqul Thistle Crumpet's Camp for Hardcore Lady Types, the Lumberjanes discover that they are trespassing on the lands of the Cloud People and they find unicorns.